19 IDENTIFICATION OF PATIENTS WITH INFLAMMATORY BOWEL DISEASE AT HIGH RISK OF URGENT CARE UTILIZATION THROUGH IBD QORUS, A LEARNING HEALTHCARE SYSTEM. (7th February 2019) - Hou, Jason K; Xu, Anthony; Oliver, Brant; Singh, Siddharth; Weatherly, Julie; Shukla, Richa; Guardado, Julia; Weaver, Alandra; Crate, Damara; Siegel, Corey; Melmed, Gil
Abstract: Background: The disease course of inflammatory bowel disease (IBD) is often associated with periods of response interrupted by flares. Identification of patients at high risk of utilization of urgent care resources may allow for proactive intervention and avoid unnecessary emergency department utilization, exposure to diagnostic radiography, steroid use, narcotic use, and hospitalizations. We hypothesized urgent care utilization is associated with patient factors and provider assessments. The aim of this study was to assess the association of a patient-reported tool and provider assessment with urgent care utilization. Methods: This study was performed as part of a breakthrough series collaborative of IBD Qorus, a learning healthcare system. Data were collected from patients from 30 participating Qorus [AW1] sites during routine clinical care from February 2018 to July 2018, and included provider global assessment of high-risk for urgent care utilization. Associations of patient factors and provider assessments with urgent care utilization were assessed using Chi-square test, univariate, and multivariate logistic regression. Patients were designated as "high risk" status for urgent care utilization for analyses a priori, using including age, gender, IBD type, IBD Manitoba Index, frequency of calls to clinic, and provider global assessment. Analyses were performed per IBD encounter. Results: A total of 7, 345 patient encounters were included in the study period. Among patients who met criteria for "high risk" status, 47% reported urgent care utilization in the prior 6 months, compared to only 3.5% of patients who were classified as "low risk". Using only provider global assessment, 59% of patients assessed as "high risk" reported urgent care utilization compared to 17% of patients who were "low risk". On univariate analyses, age, gender, IBD type, patient-reported wellbeing, Manitoba IBD Index, greater than four calls to the provider's office in the past month, and provider global assessment, were all statistically significantly associated with use of urgent care in the preceding 6 months. On multivariate analyses, age, patient-reported wellbeing, patient calls, and provider global assessment remained significant (Table 1). The factor most associated with urgent care utilization was provider assessment (OR 3.65, 95% CI 3.13-4.27). Conclusions: Patient and provider assessments were associated with recent urgent care utilization among patients with IBD. The ability to identify IBD patients who are at high risk of urgent care utilization may allow providers to proactively address symptoms and potentially decrease emergency department utilization and unnecessary exposure to steroids, radiation, and narcotics. These factors will be studied prospectively as part of the IBD Qorus learning healthcare system.